PENTINGNYA KATEKESE PERSIAPAN PERKAWINAN BAGI CALON PASUTRI MUDA DALAM MEWUJUDKAN KELUARGA YANG HARMONIS - Paseno, Inelta Vianney; Palimbo, Hendrik (Jurnal Euntes, 2023)
Matrimony is a sacrament as well as a covenant that binds a man and a woman in a sacred bond. They are no longer two but one. This article is an attempt to explore and explain the Catholic Church’s understanding, preparation, and concern for the people who will carry out the holy bond of a matrimony. The method used in this study is a qualitative method through reading various reliable sources of literature. Through such kind of method and techniques, this research arrived at a suggestion about the importance of participating in the Marriage Preparation Catechesis for prospective married couples, especially young prospective married couples, in order to create a harmonious family.   Key words: Marriage, Catholic Church, Church Documents, Husband and wife